The national jurisprudential criteria regarding the prevalence of registered personal right over unregistered real law: special consideration of legal security and public registry faith - Vigo Saldaña, Flaminio Gilberto (2009)
When a personal property right is enforced against a previously registered personal right, case law prefers the first one. Notwithstanding, an opposite stance is assumed indicating that the enforceability of rights should not occur based on the nature of the enforced rights but based on the publicity they had; otherwise, in most of the cases, the message would be to favor frauds and collusion with the debtor intending to evade the creditor’s right